2021
DOI: 10.3390/jcm10143042
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Female Patients Following Ileal Neobladder and Ileal Conduit: Where Are We?

Abstract: Women undergoing a radical cystectomy (RC) followed by a urinary diversion (UD) for bladder cancer (BC), experience a substantial reduction in health-related quality of life (HRQOL). At present, studies comparing long-term QOL outcomes for different UD methods in female patients are lacking. We summarize the current state of the QoL assessment in female patients after an RC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…When comparing the results of patients with incontinent and continent urinary diversions in our study cohort, no significant differences were found in the EORTC questionnaire. This is in accordance with the findings of several authors in the past who found no significant diversion-related differences regarding QoL [ 21 23 ], whereas other studies have shown better results for either incontinent [ 24 ] or continent [ 25 ] diversions. Therefore, whether the type of urinary diversion really influences the rates of sexual function and QoL remains unclear [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…When comparing the results of patients with incontinent and continent urinary diversions in our study cohort, no significant differences were found in the EORTC questionnaire. This is in accordance with the findings of several authors in the past who found no significant diversion-related differences regarding QoL [ 21 23 ], whereas other studies have shown better results for either incontinent [ 24 ] or continent [ 25 ] diversions. Therefore, whether the type of urinary diversion really influences the rates of sexual function and QoL remains unclear [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several groups have investigated the impact of urinary diversion type (continent versus incontinent) on overall postoperative QOL, including SF. Biardeau et al and Siracusano et al found that women receiving orthotopic neobladder (ONB) were younger, more often sexually active after surgery and reported higher physical functioning on self-administered QOL surveys than women with an ileal conduit (IC) [35,36]. However, on all other components of the global functioning and BC-specific questionnaire domains, no significant differences between groups were noted [35,36].…”
Section: Survivorship and Patient Reported Outcomesmentioning
confidence: 99%
“…For example, Leminski et al [45] found that incorporating a preoperative support group led to a significantly lower incidence of postoperative depression. Depression or anxiety related to body image alterations, hypercontinence or incontinence, changes to libido and sensation, as well as anatomic vaginal changes are all major contributors to female-specific sexual health following RC [34 ▪▪ ,36,42]. Many of these issues can be addressed either by the provider or by appropriate referrals to a better-suited healthcare team member, such as a pelvic floor physical therapist or sexual medicine therapist [46].…”
Section: Survivorship and Patient Reported Outcomesmentioning
confidence: 99%
“…Such changes and quality of life (QoL) of patients are commonly studied through retrospective clinical evaluations and rarely with longitudinal studies. To date, studies focusing on functional outcomes, sexual function, and health-related QoL for female patients are lacking especially in the short term, although as a whole statistically significant worse overall survival, recurrence-free survival, and cancer-specific survival are reported in comparison to male patients ( 4 ). The aim of this study was to evaluate the QoL in female patients in the first 6 months postoperatively with IC or ONB utilizing EORTC QLQ-C30 (QLQ-30) and Short-Form 36 (SF-36) questionnaires in a prospective longitudinal fashion.…”
Section: Introductionmentioning
confidence: 99%